Triptycene-Based porous metal-assisted salphen organic frameworks$iInfluence of the metal ions on formation and gas sorption - Reinhard, Dennis; Zhang, Wen-Shan; Vaynzof, Yana; Rominger, Frank; Schröder, Rasmus R.; Mastalerz, Michael (Chemistry of materials, 2018)
Porous organic polymers (POPs) are chemically and thermally robust materials and have been often investigated for their gas sorption properties. From the related field of metal-organic frameworks (MOFs) it is known that open ligation sites at metal centers can enhance the performance of gas sorption significantly, especially the selectivity toward one gas of a binary mixture, such as CO2/N2 or CO2/CH4. POPs that contain metal centers are rarer. One possibility to introduce metals into POPs is by the synthesis of metal-assisted salphen organic frameworks (MaSOFs), where the framework development is associated with the formation of the metal-salphen pockets. Based on a hexakissalicylaldehyde, a variety of three-dimensional isostructural porous MaSOFs with different metal ions (Zn2+, Ni2+, Cu2+, Pd2+, and Pt2+) are introduced. All compounds show a very similar pore structure and comparable specific surface areas, which make these MaSOFs ideal candidates to study the influence of the nature of the incorporated metal center on gas sorption selectivity. Due to the environmental importance, the adsorption of CO2 in comparison to N2 and CH4 was extensively studied. Depending on the metal ions, the heat of adsorption was different as well as the Henry and IAST selectivities. Cu-MaSOF100 for instance shows a high Qst of 31.2 kJ mol-1 for CO2 and an uptake of 14.9 wt % at 1 bar and 273 K. The IAST selectivity of CO2/N2 for an 80/20 mixture is with SIAST = 52 very high for a metal containing POP and even comparable to some of the best performing MOFs. The MaSOFs are stable even in boiling water. This, as well as the simple synthesis, makes them potential good candidates for CO2 removal of binary mixtures.